Global profiling of cellular targets of gambogic acid by quantitative chemical proteomics. Issue 97 (17th November 2016) - Zhou, Yiqing; Li, Weichao; Zhang, Xixi; Zhang, Haibing; Xiao, Youli
Abstract : Gambogic acid has shown significant potential as an anti-cancer and anti-inflammatory compound, here we report that the target profiling of gambogic acid in human cancer cells via quantitative chemical proteomics. Abstract : Gambogic acid has shown significant potential as an anti-cancer and anti-inflammatory compound; however, the molecular mechanism underlying the actions of gambogic acid, particularly its cellular target profiles, has not been investigated. In this study, we report the proteome-wide profiling of potential cellular targets of gambogic acid using quantitative mass spectrometry-based chemical proteomics. The target profiles of gambogic acid in living HeLa and K562 cells were identified, which strengthened our understanding of the mode of actions of the phytochemical.